Determinant Analysis of Decrease In Manufacturing Export Value Amid Depreciation of Rupiah Exchange Rate - Nanik Ika Nurhayati (Economics Development Analysis Journal, 2017)
Indonesia uses a system of floating exchange rate. The depreciation of the exchange rate, in which the value of domestic currency decreases and the value of foreign currency increases, will increase the export. The high depreciation of Rupiah should be able to increase the competitiveness of Indonesia’s export products, especially the manufacturing exports that have the greatest contribution to the total exports. However, what has happened in recent years is very different. The depreciation of Rupiah value cannot spur the value of Indonesia’s manufacturing exports. Based on the fact above, the research is entitled "Determinant Analysis of Decrease in Manufacturing Export Value amid Depreciation of Rupiah Exchange Rate. This research uses time series secondary data for the quarterly period of 2006Q1-201Q3 that is obtained from Bank Indonesia, International Financial Statistics, and World Bank. The analytical technique used is the OLS (Ordinary Least Square) method using E-Views 6. The results of this research indicate that the Rupiah exchange rate and the GDP growth of the export destination countries have a positive relationship but are insignificant to the manufacturing exports, while the inflation rate is negative and insignificant to the value of manufacturing exports. Meanwhile, the raw material import has a significant positive effect on manufacturing exports. This shows that the Indonesia’s manufacturing exports still depend on the imported raw materials. Related to this fact, the government must take a strategic step in the short term to increase the non-oil exports, especially the exports of manufactured products that are the high value-added export products.